2020
DOI: 10.1101/2020.03.19.997262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Htr6 and Sstr3 ciliary targeting relies on both IC3 loops and C-terminal tails

Abstract: G protein-coupled receptors (GPCRs) are the most common pharmacological target in clinical practice. To perform their signaling functions, many GPCRs must accumulate at primary cilia, microtubule-based plasma membrane protrusions that work as cellular antennae. Despite their great importance, the molecular mechanisms underlying GPCR ciliary targeting remain poorly understood. Serotonin receptor 6 (Htr6) and somatostatin receptor 3 (Sstr3) are two brain-enriched ciliary GPCRs controlling cognition and involved … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Our results indicate that the C terminus of SSTR3 is required for TULP3-mediated ciliary localization. Consistent with this observation, Barbeito et al (2021) recently reported that a proximity labeling assay indicated association of TULP3 with the C terminus of SSTR3. The tubby protein family includes TUB and TULP1-4.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our results indicate that the C terminus of SSTR3 is required for TULP3-mediated ciliary localization. Consistent with this observation, Barbeito et al (2021) recently reported that a proximity labeling assay indicated association of TULP3 with the C terminus of SSTR3. The tubby protein family includes TUB and TULP1-4.…”
Section: Discussionsupporting
confidence: 63%
“…During the course of our study, Barbeito et al (2021) reported the presence of a C-terminal CLS in SSTR3 and HTR6, expressed in IMCD3 cells. This work, which was focused mainly on HTR6, used some different approaches from ours to characterize the CLS, resulting in some different conclusions as well as some in common.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…CD63 is an enriched marker in intraluminal vesicles (ILVs) contained into MVB and exosomes and has been widely used to study MVB secretory traffic in both living and fixed cells(2,17).The FMNL1 interfering vector (shFMNL1-HA-YFP) and FMNL1-interfering, YFP-FMNL1bWT expressing vector (shFMNL1-HA-YFP-FMNL1bWT) were previously described (35) and generously provided by Dr. Billadeau. shFMNL1-HA-YFP-FMNL1βS1086A and shFMNL1-HA-YFP-FMNL1βS1086D mutants were generated by site-directed mutagenesis, as previously reported(74). Briefly, overlap extension PCR was used to introduce the desired mutations into a 900 bp SalI-NotI fragment, which was then used to replace the corresponding wild type sequence in shFMNL1-HA-YFP-FMNL1β-WT.…”
mentioning
confidence: 99%
“…CD63 is an enriched marker in intraluminal vesicles (ILVs) contained into MVB and exosomes and has been widely used to study MVB secretory traffic in both living and fixed cells (2, 17).The FMNL1 interfering vector (shFMNL1-HA-YFP) and FMNL1-interfering, YFP-FMNL1bWT expressing vector (shFMNL1-HA-YFP-FMNL1bWT) were previously described (35) and generously provided by Dr. Billadeau. shFMNL1-HA-YFP-FMNL1βS1086A and shFMNL1-HA-YFP-FMNL1βS1086D mutants were generated by site-directed mutagenesis, as previously reported(73). Briefly, overlap extension PCR was used to introduce the desired mutations into a 900 bp SalI-NotI fragment, which was then used to replace the corresponding wild type sequence in shFMNL1-HA-YFP-FMNL1β-WT.…”
mentioning
confidence: 99%